Surname analysis in the study of the identities of two communities in the Susa Valley (Turin) in the 18th and 19th centuries (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: surnames; relationship; Alpine populations